РАЗРАБОТКА МЕТОДА ВИЗУАЛЬНОЙ КЛАССИФИКАЦИИ ИЗДЕЛИЙ С ПОМОЩЬЮ КОМПЬЮТЕРНОГО ЗРЕНИЯ - Ураимов Мухаммаддиёр Боходир угли; Локтев Даниил Алексеевич (Journal Park Publishing, 2025)
The paper presents the development of a visual product classification method using computer vision technologies and deep convolutional neural networks. The proposed approach is designed for industrial quality control systems and allows automatic recognition of product types based on images. The model achieved high classification accuracy and demonstrated potential for real-world implementation.
Keywords: computer vision, image classification, convolutional neural network, automation, quality control.